Philosophical Foundations of P. Dovydaitis’ Gnoseological Conception - Balčius, Jonas (Problemos, 1988)
An attempt is made to reveal the gnoseological premises of P. Dovydaitis’ (1886- 1942) views. It is shown that the Lithuanian neo-Thomist treats religious, philosophical, and scientific knowledge as a synthetic cognitive whole embracing all reality. The latter methodological premise is said to base P. Dovydaitis’ gnoseological conception concerning the possibilities and limits of human understanding. The short-comings of the conception are pointed out by the author of the article.